Freilebende marine Nematoden von den Sunda-Inseln. I. Enoplidae. (Papers from Dr. Th. Mortensen's Pacific Expedition 1914-16 53) (edited by H. A. KREIS) - Micoletzky, H. (Vidensk. Meddr dansk naturh. Foren., 1930)
Locality: Sunda-Inseln, See text; Cabinet:
Locality: Sunda-Inseln; NeMys doc_id: 3927